The Concept of The Urban Flaneur in The Relationship of Cinema and Architecture - Temel, Selda Cansu; Polatoğlu, Çiğdem (Journal of History Culture and Art Research, 2023)
The experience of time and space is one of the main veins of cinema and architecture. The area where the two disciplines intersect in this direction can be read within the framework of the images created by the films through flowing images. The created images allow the perception and reading of the space. The way the cinema presents space expansions through montage leads to a similarity between the experience of a flaneur traveler in the city and the cinema audience. The study, which developed within the framework of the idea that cinematographic approaches are an effective tool in reading individual perception in urban space, aims to read the ways in which the relationship of the individual with the place as a traveling observer is transformed into information with cinematographic tools, within the framework of the experience of the urban dweller of flaneur. In this direction, the way the films show the city as moving during the walk was tried to be read with the view of the city of flaneur. In line with the existence of the concept of flaneur in films, the silent and sound cinema periods are handled as two separate groups. In the silent cinema era, the camera viewfinder's wanderings in urban spaces are replaced by the character and narrative plot in the sound cinema era. As a result of the study, it was seen that an exemplary reading associated with the urban flaneur is possible in terms of the way the cinema uses and presents the city as moving fragments and the perception of the architectural space based on movement.